Differentiating meningioma grade by imaging features on magnetic resonance imaging. (February 2018) - Hale, Andrew T.; Wang, Li; Strother, Megan K.; Chambless, Lola B.
Highlights: Tumor volume is the most predictive feature of higher-grade meningioma. Presence of tumor necrosis is predictive of higher-grade meningioma. Increased peri-tumoral edema is predictive of higher-grade meningioma. Tumor location along the falx or convexity is predictive of higher-grade meningioma. Abstract: Atypical meningioma has an aggressive clinical course. Distinguishing atypical from benign meningioma preoperatively could affect surgical planning and improve treatment outcomes. In this study, we examined whether pre-operative magnetic resonance imaging (MRI) features could distinguish between benign and atypical meningioma. Imaging factors analyzed included peritumoral edema, the presence of a draining vein, tumor necrosis, tumor location and tumor volume. Using univariate analysis, the most striking predictor of grade was tumor volume (p < .001). When adjusting for the degree of peritumoral edema, volume remained a positive predictor of higher histological grade meningioma (p = .042) and was the strongest single predictor of higher-grade meningioma in this study. Additional imaging features associated with increased risk for atypical pathology in univariate analysis included the presence of tumor necrosis ( p = .012), peritumoral edema ( p = .022) and location along the falx and convexity (p = .026). Despite statistically significant associations using univariate analysis, in multivariate analysis, we found that only presence of peritumoral edema was predictive of a higher-grade meningioma. Further multivariate analyses suggests that edema, draining vein and necrosis are all positive predictors of tumor volume (p < .0001). Overall, these data suggest that radiographic features including presence of tumor necrosis, and tumor location along the falx or convexity may be predictive of higher-grade meningioma when considered alone. However, most strikingly, our data point to tumor volume as the most robust pre-operative indicator of higher-grade meningioma.